DISTRIBUSI LONGITUDINAL DAN STRUKTUR POPULASI Rasbora spp. DI SUNGAI BANJARAN KABUPATEN BANYUMAS - Titis Amelia; Windiariani Lestari; Agus Nuryanto (Scripta Biologica, 2014)
Rasbora is a genus of freshwater fish of the family Cyprinidae. Three species belonging to this genus were found in Java Island; R. aprotaenia, R. lateristriata, and R. argyrotaenia. Rasbora inhabits clear running water with sandy and gravel bottom. This study aimed to determine the longitudinal distribution of Rasbora spp. based on their species richness and abundance at Banjaran River; to determine the population structure of Rasbora spp based on their body weight, standard and total length; and to identify interactions between physical-chemical factors with species richness and abundance of Rasbora spp. This research was a survey, with purposive random sampling technique applied to collect samples. The research divided the study sites into five stations based on their altitude and topography. The Cluster Analysis was calculated based on species richness and relative abundance of Rasbora spp., while the longitudinal distribution and the population structure were presented descriptively. The interaction between the physical-chemical factors and the species richness and abundance of Rasbora were analyzed using Principal Component Analysis (PCA). Thi study found two species of Rasbora, namely Rasbora argyrotaenia and Rasbora lateristriata with 80 and 2 individuals respectively. R. argyrotaenia was distributed longitudinally along Banjaran River. Meanwhile, R. latestriata was only found at the upstream. Based on the body weight, the population of R. argyrotaenia at the station three were found highest by the average body weight of 1–6 gr of a total 31 individuals. The maximum measurements of the standard length were observed at the station 3 with a range of diameter 4.0–5.9 cm of 30 individuals. The total length were also found at the station 3 with a range of measuremtnt 5.0–7.9 cm of 33 individuals. R. latestriata was found only two individual with body weights measured were 9 gr and 10 gr, the standard lengths were 7.6 and 8.5 cm, and the total lengths were 9.5 and 10.5 cm. The distribution of R. argyrotaenia was influenced mostly by pH, the speed of the water, and DO. The presence of R. lateristriata was influenced primarily by BOD and depth.